Assessment of the stress-strain state of profile joints of machine components - V. A. Ilinykh; V. Yu. Lineytsev; O. S. Belkina; E. V. Nepomnyashchikh (Омский научный вестник)
The article presents the results of studies of profile joints of mechanisms and machines for rigidity and strength. The device is based on the use of fixed and movable profile connections designed to transmit torque. Profile joints with a guaranteed gap are considered, made on the basis of an equiaxial contour of the P3, P5 type and a curved contour of the PC4 type, which have received the most widespread introduction in the nodes of metal-cutting machines and other machines manufactured in Russia, as well as Hungary, Germany and the DPRK. Using a well-known technique designed to assess the stress-strain state (VAT) of the parts of profile joints, calculations are performed according to the criteria of operability for strength and stiffness of hubs (bushings) with different wall thicknesses. The analysis of the results of the calculation of strength and stiffness is carried out using the example of the P3 profile. When stretching the hub from the action of spacer forces, the geometric shape, the nominal size of the covered part, the wall thickness of the covering part, as well as the magnitude of the external load transmitted by the connection in static are taken into account. The permissible values of the thickness of the walls of the hub (bushings) of the joint are determined to ensure the rigidity of the hub under tension from the action of external loads. As a result of the research, the influence of the thickness of the hub walls for the studied shapes of the joint parts on the values of the transmitted torque is established. For example, a change in the thickness of the hub wall from 15 to 3 mm for a normal range of shaft mounting diameters causes the sleeve to stretch radially up to 50 microns in the range of transmitted torques from 5 to 600 Nm.